1985
DOI: 10.1073/pnas.82.20.7111
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating effects of murine nerve growth factor in the peripheral and central nervous systems of Xenopus laevis tadpoles.

Abstract: The present investigation was directed toward exploration of the spectrum of action of murine nerve growth factor (m-NGF) in peripheral cells and neurons in the central nervous system (CNS) ofXenopus laevis tadpoles. It was found that systemic m-NGF injections elicit growth and differentiative effects not only on sensory and sympathetic nerve cells but also on several populations in the CNS. The finding that aminergic and peptidergic neurons in brain centers are highly receptive to m-NGF activity provides evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Some earlier studies also showed that mouse submandibular glands synthesize and release into the saliva large quantities of NGF and that synthesis of this protein is controlled by testosterone and thyroxine [reviewed in 48 ]. Later, Levi-Montalcini and Aloe found that systemic murine NGF injections lead to growth and differentiation of sensory and sympathetic nerve cells as well as on several populations of cells in the central nervous system of Xenopus laevis tadpoles [49] . Using animal model of aggression Spillantini et al detected increased NGF mRNA and protein production in the hypothalamus [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies also showed that mouse submandibular glands synthesize and release into the saliva large quantities of NGF and that synthesis of this protein is controlled by testosterone and thyroxine [reviewed in 48 ]. Later, Levi-Montalcini and Aloe found that systemic murine NGF injections lead to growth and differentiation of sensory and sympathetic nerve cells as well as on several populations of cells in the central nervous system of Xenopus laevis tadpoles [49] . Using animal model of aggression Spillantini et al detected increased NGF mRNA and protein production in the hypothalamus [50] .…”
Section: Discussionmentioning
confidence: 99%
“…While NGF is the prototypical neurotrophic and survival factor for both sympathetic and sensory neurons during development [6], it is involved in inflammatory hyperalgesia in adulthood [7], [8]. Previous study from our laboratory has shown NGF is produced in the muscle after LC and plays a pivotal role in DOMS [4].…”
Section: Introductionmentioning
confidence: 97%
“…Monoclonal antibodies (192-IgG; a generous gift from E. M. Johnson, Jr., Washington University, Saint Louis) were radioiodinated with Na1251 (Amersham) by the chloramine-T procedure (22)(23)(24), and 1SI-labeled antibodies (125I-192-IgG)…”
Section: Methodsmentioning
confidence: 99%